A natural goldmine of binding proteins and soluble receptors simplified their translation to blockbuster drugs, all in one decade - Novick, Daniela (Frontiers in Immunology, 2023)
Human urinary proteins are a goldmine of natural proteins a feature that simplifies their translation to biologics. Combining this goldmine together with the ligand-affinity-chromatography (LAC) purification method, proved a winning formula in their isolation. LAC specificity, efficiency, simplicity and inherent indispensability in the search for predictable and unpredictable proteins, is superior to other separation techniques. Unlimited amounts of recombinant cytokines and monoclonal antibodies (mAb) accelerated the “triumph”. My approach concluded 35 years of worldwide pursuit for Type I IFN receptor (IFNAR2) and advanced the understanding of the signal transduction of this Type of IFN. TNF, IFN-g and IL-6 as baits enabled the isolation of their corresponding soluble receptors and N-terminal amino acid sequence of the isolated proteins facilitated the cloning of their cell surface counterparts. IL-18, IL-32, and heparanase as the baits yielded the corresponding unpredictable proteins: the antidote IL-18 Binding Protein (IL-18BP), the enzyme Proteinase 3 (PR3) and the hormone Resistin. IFN-b proved beneficial in Multiple Sclerosis and is a blockbuster drug, Rebif®. TNF mAbs translated into Remicade® to treat Crohn’s disease. Enbrel® based on TBPII is for Rheumatoid Arthritis. Both are blockbusters. Tadekinig alfaTM, a recombinant IL-18BP, is in phase III clinical study for inflammatory and autoimmune diseases. Seven years of continuous compassionate use of Tadekinig alfaTM in children born with mutations (NLRC4, XIAP) proved life-saving and is an example of tailored made medicine. IL-18 is a checkpoint biomarker in cancer and IL-18BP is planned recently to target cytokine storms resulting from CAR-T treatment and in Covid 19.